ZnO nanorod arrays assembled on activated carbon fibers for photocatalytic degradation: Characteristics and synergistic effects. (December 2020) - Luo, Sha; Liu, Chunwei; Zhou, Sui; Li, Wei; Ma, Chunhui; Liu, Shouxin; Yin, Wang; Heeres, Hero Jan; Zheng, Weiqing; Seshan, Kulathuiyer; He, Songbo
Abstract: Well-aligned ZnO nanorod arrays were assembled on activated carbon fibers by a stepwise sequence of sol-gel and hydrothermal synthesis methods. These ZnO nanorod arrays on activated carbon fibers having different characteristics such as surface area, rod concentration, aspect ratio and defect level, were applied as catalysts for the photodegradation of an aqueous methylene blue solution. They showed very promising methylene blue adsorbility in the dark ( ca . 0.025–0.031 mg methylene blue m −2 catalyst, vs . 0.072 mg methylene blue m −2 activated carbon fibers). Significantly, the defect level of ZnO nanorod arrays has a major effect on the turnover frequency compared to other characteristics. A synergistic effect between activated carbon fibers and ZnO nanocrystals on enhancing turnover frequency was more significant for the well-assembled ZnO nanorod arrays on activated carbon fibers catalysts compared to the mechanically mixed ZnO powder with activated carbon fibers catalyst. Further, turnover frequency for the ZnO nanorod arrays on activated carbon fibers (0.00312 molmethylene blue molZnO −1 h −1 ) was twice higher than that for the corresponding bare ZnO nanorod arrays, and 3 times higher than that for a commercial ZnO powder. In addition, ZnO nanorod arrays on activated carbon fibers show high degradation (77.5%) and mineralization (55.0%) levels for methylene blue, and also good reusability (or stability) as demonstrated by a sequential 5-time recycle routine. These outstanding features indicate that activated carbon fibers supported ZnO nanorod arrays have significant potential to be used as catalysts for photodegradation. Graphical abstract: Image 1 Highlights: MB adsorbability per surface area of the synthesized ZnO NRAs is 39% of that of ACFs. MB adsorbtion on ZnO NRAs/ACFs increases linearly with surface area. Defect level of ZnO NRAs plays more role than other characteristics in TOF of ZnO NRAs/ACFs. ZnO NRAs/ACFs show higher synergistic effect than the mechanically mixed ZnO-ACFs. ZnO NRAs/ACFs after 5 recycles show comparable TOF with that for the fresh ZnO NRAs.